PENGARUH KUALITAS PRODUK, PERSEPSI HARGA, DAN PROMOSI MEREK TERHADAP MINAT BELI KONSUMEN AQUA DI BATAM - Andi M. Lutfi; Adnan Suhardis; Sri Yanti; M. Tommy Rumengan (Program Studi Akuntansi, 2022)
The purpose of this study was to determine and analyze the effect of Product Quality (X1), Price Perception (X2) and Brand Promotion (X3) against Consumer Buying Interest (Y) in Batam. The research method used is quantitative methods and the data analysis method used is multiple linear regression analysis using the help of SPSS 25.0 program. The population in this study were Aqua’s customer in Batam. By using the Slovin formula we obtained a sample of 100 consumers. The results of testing the hypothesis show that Product Quality has a significant effect on Consumer Buying Interest, Price Perception has a significant effect on Consumer Buying Interest and Brand Promotion has a significant effect on Consumer Buying Interest. Based on the multiple linear regression statistical test, the coefficient of determination (R2) is 0.290, meaning that 29% of the variables of Product Quality, Price Perception, and Brand Promotion affect Consumer Buying Interest.